Progress in Research on the Effect of Melatonin on Postoperative Cognitive Dysfunction in Older Patients - Wei, Yuqing; Zhang, Chunlu; Wang, Danyang; Wang, Chengping; Sun, Lin; Chen, Peng (Frontiers in Aging Neuroscience, 2022)
Postoperative cognitive dysfunction (POCD) is a common complication of the central nervous system in elderly patients after operation. It will prolong the length of stay, reduce the independence and quality of daily life, and increase the risk of death. However, at present, there is a lack of safe and effective ideal drugs for the prevention and treatment of POCD. Melatonin is one of the hormones secreted by the pineal gland of the brain, which has the functions of regulating circadian rhythm, anti-inflammation, anti-oxidation, anti-apoptosis, and so on. Some recent studies have shown that MT can prevent and treat POCD by adjusting circadian rhythm, restoring cholinergic system function, neuroprotection, and so on. This article will introduce POCD, melatonin and the mechanism of melatonin on POCD, respectively, to provide a basis for clinical prevention and treatment of POCD in the elderly.